2011
DOI: 10.1016/j.jss.2011.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Race Disparities in Wilms Tumor Incidence and Biology

Abstract: Background Wilms tumor (WT) is thought to arise in children of black African ancestry with greater frequency than whites. To clarify the biological basis for race disparities in WT, we first verified that black children residing in Tennessee have an increased incidence of WT, and second, established molecular profiles in WT that are specific to race. Materials and Methods To assess race disparities in WT epidemiology, the Tennessee Cancer Registry (TCR) was queried for all in-state patients less than 20 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 20 publications
1
41
0
Order By: Relevance
“…The classification of specimens according to the race based on MSI peptide spectra represents an early preview into the biological basis for epidemiologic observations in WT [43].…”
Section: Cancer Research and Neurological Disordersmentioning
confidence: 99%
“…The classification of specimens according to the race based on MSI peptide spectra represents an early preview into the biological basis for epidemiologic observations in WT [43].…”
Section: Cancer Research and Neurological Disordersmentioning
confidence: 99%
“…Denys-Drash syndrome, hemihypertrophy, and several overgrowth syndromes (i.e., Beckwith-Wiedemann, Simpson-Golabi-Behmel, and Perlman syndromes) have been associated with WT [2,6]. In addition, WT has also been linked to congenital conditions outside the context of known genetic syndromes, including mental retardation and urogenital malformations [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that African-American children may be affected with WT proportionally more often than Caucasian-or Asian-Americans [7,9,5]. One study implied that this disparity may be due, in part, to a higher prevalence of the predisposing congenital anomalies and syndromes among African-American children [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We thank these talented academic surgeons in advance for their service and support of the Journal [19][20][21][22][23][24][25][26][27][28][29].…”
mentioning
confidence: 99%